Confirmed occurrence and DNA barcoding of the Indo-Pacific Slender Gecko, Hemiphyllodactylus typus Bleeker, 1860 (Squamata, Gekkonidae) in Vietnam - Chau, Phuc Hong; Nguyen, Vu Dang Hoang; Dang, Khoa Dang; Nguyen, Truong Minh Nhat; Ngon, Lam Quang; Phan, Lan Vu Phuc; Huynh, Hoan Duc; Grismer, L. Lee; Nguyen, Thao Thi Phuong (Zootaxa, 2026)
Hemiphyllodactylus Bleeker is a complex taxon characterized by species with small body sizes, low population densities, inconspicuous morphologies, cryptic coloration, and overall difficulty of detection within their native ecosystems. The genus is one of the most diverse and fastest growing gekkonid genera — as of 2025, a total of 69 species have been described. Most species within this genus are endemic to restricted regions, whereas Hemiphyllodactylus typus Bleeker, 1860 has a remarkably broad distribution, ranging from the Indian Ocean to the Pacific Ocean. Previously, H. typus had been recorded in Vietnam by René Bourret under the name H. typus chapaensis from Sapa, Lao Cai. However, a subsequent study by George R. Zug identified this specimen as H. yunnanensis (Boulenger, 1903). Another instance of H. typus in Vietnam has been recorded, inferred solely from molecular analysis. Nevertheless, we re-examined the sequence of this specimen and confirmed that it does not belong to species H. typus. Our surveys in Can Gio Mangrove Biosphere Reserve, Ho Chi Minh City and My Phuoc’s Melaleuca Forest, Can Tho City, Vietnam recovered specimens that, following both morphological and molecular analyses using the NADH dehydrogenase subunit 2 gene (ND2), are conclusively identified as H. typus. Thus, this study confirms the occurrence of H. typus in Vietnam for the first time. Additionally, we established DNA barcoding based on the cytochrome c subunit 1 gene (COI) to support identification and conservation management of biodiversity and discuss the potential for range expansion of this species within Vietnam, as well as hypotheses regarding its possible unisexual reproduction.